O02 Developmental pharmacogenetics of SLCO2B1 on montelukast pharmacokinetics in chinese children. Issue 6 (17th May 2019) - Li, Q; Wang, K; Shi, H-Y; Y-E, Wu; Zhou, Y; Kan, M; Zheng, Y; Hao, G-X; Yang, X-M; Yang, Y-L; L-Q, Su; Wang, X-L; et al.
Abstract : Background: Montelukast, a potent orally selective leukotriene-receptor antagonist, inhibits the action of cysteinyl-leukotriene in patients with asthma.Although pharmacokinetic studies of montelukast have been reported in Caucasian adults and children, and showed significant inter-individual variability on pharmacokinetics.None of pharmacokinetic study has been explored in Chinese children. Given the potential inter-ethnic difference, the purpose of this study was to evaluate the effects of developmental factors and pharmacogenetics of CYP2C8 and SLCO2B1on Montelukast pharmacokinetics in Chinese paediatric patients. Methods: After oral administration with montelukast, opportunistic samples were collected from asthma children and plasma concentrations were determined by high performance liquid chromatography coupled with fluorescence detector (HPLC-FLD) method. Population pharmacokinetic analysis was performed using a nonlinear mixed-effects model approach (NONMEM V 7.2.0) and variants of CYP2C8 and SLCO2B1 were genotyped. Results: Fifty patients (age range 0.7–10.0 years) with asthma were enrolled in this study. The clearance of montelukast was significantly higher in subjects with SLCO2B1 c.935GA and c.935AAgenotype compared withSLCO2B1 c.935GGsubjects (0.94±0.26 versus 0.77±0.21, p=0.020). Weight was also found to be significantly corrected with montelukast clearance (p 0.0001). Conclusions: The developmental pharmacogenetics of montelukast in Chinese children was evaluated. Weight and SLCO2B1 genotype showed independently significant impacts on theclearanceofmontelukast. Disclosure(s): Nothing to disclose.